(untitled) (Global Journal of Medical Research, 2015)
Kawasaki disease is an acute systemic vasculitis of unknown cause that affects mainly infants and children. Coronary artery lesions (CAL) are one of the most important complications of this disease. An appropriate therapy during acute phase of Kawasaki disease to prevent large CAL has not been established. Recent studies disclosed that aspirin and flurbiprofen appeared to have a negative impact on the suppressive effects of initial intravenous immunoglobulin (IVIG) therapy on CAL development in the acute phase of Kawasaki disease and that an initial single IVIG therapy with delayed administration of anti-inflammatory drugs might be useful for prevention of large CAL. Furthermore, recent study disclosed that variable factors including IVIG resistance, responsiveness, and relapse of disease were associated with CAL complications and that an initial single IVIG therapy may be useful for the prevention of large CAL caused by different factors of Kawasaki disease.